A Security Proof of Measurement Device Independent Quantum Key Distribution： From the View of Information Theory - 李芳毅 银振强 李宏伟 陈巍 王双 温浩 赵义博 韩正甫 (Chinese physics letters, 2014)
Although some ideal quantum key distribution protocols have been proved to be secure, there have been some demonstrations that practical quantum key distribution implementations were hacked due to some real-life imperfections. Among these attacks, detector side channel attacks may be the most serious. Recently, a measurement device independent quantum key distribution protocol [Phys. Rev. Lett. 108 （2012） 130503] was proposed and all detector side channel attacks are removed in this scheme. Here a new security proof based on quantum information theory is given. The eavesdropper＇s information of the sifted key bits is bounded. Then with this bound, the final secure key bit rate can be obtained.